Evaluasi Koleksi Berdasarkan Silabus Program Studi Bimbingan dan Konseling Islam di UPT Pusat Perpustakaan IAIN Surakarta - Maslahah, Khoirul; Rahmawati, Nushrotul Hasanah (UI Scholars Hub, 2018)
This study aims to identify and analyze the availability collections of Library Center of IAIN Surakarta, and the factors that influence the availability of materials teaching for Islamic Counseling and Guidance Study Programme. This research is a qualitative and quantitative methode. Data analysis was carried out using the checklist and interview. Based on the research, 49,5% availability collections for institute level courses, and 44.7% for departement level. Based on the findings research, Library Center of IAIN Surakarta collections has not fulfilled the need for compulsory teaching materials. This is caused by several factors: the procurement of library materials is carried out only once a year; low provision of funds for library; and the lack of coordination and cooperation between Library Center of IAIN Surakarta managers and study programs in the determination of proposed titles book.